2022
DOI: 10.3390/nu14132682
|View full text |Cite
|
Sign up to set email alerts
|

The Cow’s Milk Related Symptom Score: The 2022 Update

Abstract: CoMiSS® was developed 7 years ago to increase the awareness of health care professionals towards the possibility that symptoms presented by infants could be related to cow’s milk. While CoMiSS was conceived mostly on theoretical concepts, data is now available from 25 clinical trials. Based on this extensive research using the tool since 2015, we aim to propose an updated CoMiSS. The evidence was reviewed, debated and discussed by 10 experts, of whom seven were part of the original group. The panel concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…Recently, the previously proposed cut-off point which indicates the likelihood that symptoms may be cow’s milk related was suggested to be lowered from ≥ 12 to ≥ 10. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the previously proposed cut-off point which indicates the likelihood that symptoms may be cow’s milk related was suggested to be lowered from ≥ 12 to ≥ 10. 9 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, CoMiSS does contain symptoms which are IgE mediated, such as urticaria but also vomiting, diarrhea and other gastrointestinal (GI) symptoms that can be either IgE as non-IgE mediated. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent meta‐analysis, CoMiSS may be a promising symptom score in CMA awareness and a useful tool in monitoring the response to a CM‐free diet (126), although it cannot be regarded as a stand‐alone CMA diagnostic test (127). However, there is a lack of agreement on which cut‐off to use (128). CoMiSS reduction following CM elimination was predictive for a reaction in the OFC to diagnose CMA as well as for monitoring symptom improvement (127).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Originally, an arbitrary cutoff of ≥12 was suggested as possibly indicating CMA, warranting an elimination diet followed by cow’s milk protein (CMP) reintroduction ( 2 ). A recent review evaluated the performance of CoMiSS in 25 clinical studies and concluded that lowering the cutoff to ≥10 was justified ( 3 ). Previous studies on CoMiSS also demonstrate that scores ≤5 are unlikely to be found in infants with CMA.…”
mentioning
confidence: 99%